Psychoemotional impacts on pediatric hospitalization: Perceptions of companions and the performance of the nursing team (Research, Society and Development, 2022)
The study aims to analyze the perceptions and the psychoemotional impact on the companions in the face of pediatric hospitalization, and the role of nursing in this process.  As a method, a systematic review of the works produced between the years 2016 to 2021 was used in the following databases: BDENF - Enfermagem, MEDLINE, LILACS, CINAHL and Index Psicologia;  for this, the PRISMA guidelines were followed, using the descriptors “child, perception, family or parents and nursing”.  Inclusion criteria were based on selecting articles that were related to the objective of interest, and were found in English, Portuguese or Spanish languages, and exclusion criteria were outlined in texts that were not articles.  In view of the results, the influence of hospitalization on the psychosocial of the companion and the pediatric patient became evident, and how fundamental the nursing team is in this process, developing and improving a humanized care that can provide the reduction of anxiety of both the pediatric patient and the patient. their companion, contributing to raising the quality of care provided, trusting and bonding, consequently improving the recovery process and reducing the chances of complications.